1998
DOI: 10.1073/pnas.95.11.6228
|View full text |Cite
|
Sign up to set email alerts
|

A role for heterodimerization in nuclear localization of a homeodomain protein

Abstract: The A mating type genes of the mushroom Coprinus cinereus encode two families of dissimilar homeodomain proteins (HD1 and HD2). The proteins heterodimerize when mating cells fuse to generate a transcriptional regulator that promotes expression of genes required for early steps in sexual development. In previous work we showed that heterodimerization brings together different functional domains of the HD1 and HD2 proteins; a potential activation domain at the C terminus of the HD1 protein and an essential HD2 D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 43 publications
2
47
0
1
Order By: Relevance
“…In S. commune, homodimerization between full-length HD1 proteins has been shown in vitro (11), and it will have to be established in the future whether this is also the case for C. cinereus. However, in an elegant study using a heterologous onion-␤-glucuronidase (GUS) expression system, Spit et al (442) demonstrated that NLSs are present in HD1 but not in HD2 proteins, which is consistent with a dual nuclear function of HD1 proteins, one in transport of HD2 proteins into the nucleus by heterodimerization and another independent of HD2 proteins. Different HD1 proteins seem to make different use of two possible NLS sequences (NLS1 and NLS2), both found C-terminal to the homeodomains (16,258,477).…”
Section: Vol 64 2000 Developmental Processes In Coprinus Cinereusmentioning
confidence: 95%
See 2 more Smart Citations
“…In S. commune, homodimerization between full-length HD1 proteins has been shown in vitro (11), and it will have to be established in the future whether this is also the case for C. cinereus. However, in an elegant study using a heterologous onion-␤-glucuronidase (GUS) expression system, Spit et al (442) demonstrated that NLSs are present in HD1 but not in HD2 proteins, which is consistent with a dual nuclear function of HD1 proteins, one in transport of HD2 proteins into the nucleus by heterodimerization and another independent of HD2 proteins. Different HD1 proteins seem to make different use of two possible NLS sequences (NLS1 and NLS2), both found C-terminal to the homeodomains (16,258,477).…”
Section: Vol 64 2000 Developmental Processes In Coprinus Cinereusmentioning
confidence: 95%
“…Different HD1 proteins seem to make different use of two possible NLS sequences (NLS1 and NLS2), both found C-terminal to the homeodomains (16,258,477). NLS1 is essential in the HD1 protein b1-1, encoded in a b gene pair (442). In contrast, NLS1 can be deleted in protein d1-1, coming from a d gene pair, as long as NLS2 is still present (13).…”
Section: Vol 64 2000 Developmental Processes In Coprinus Cinereusmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterodimerization of an HD1 with an HD2 protein is possible between allelic versions of different specificities present in one cell. The heterodimer creates an active transcription factor necessary for the activation of the target genes of the A mating type pathway (3,50,51,77,106).…”
Section: Molecular Structure Of a Mating Type Genesmentioning
confidence: 99%
“…Cell-cell fusion-induced formation of a transcriptional regulatory complex from components contributed by each fusion partner is employed by some fungi (Johnson 1995;Kamper et al 1995;Spit et al 1998;Vershon and Pierce 2000). After formation of a diploid cell in Saccharomyces cerevisiae, the homeodomain protein MAT␣2 from the haploid ␣ cell and the transcription factor a1 from the haploid a cell form a complex that represses ␣-specific and a-specific genes and eventually (and probably indirectly) brings about meiosis (Johnson 1995;Vershon and Pierce 2000).…”
Section: A Model For Gsp1 Regulation Of Zygote-specific Genesmentioning
confidence: 99%